Probability Oscillations And Its Importance For Non–Zero θ13 Value - Kaur, Paramjot (My University, 2012)
According to standard model, neutrinos are massless but from the beyond standard model facts it has proved that neutrinos has some mass. Neutrino oscillations are sign of massive neutrinos and they oscillate in vacuum as well as in matter. A probability oscillation in vacuum differs from matter because of the interactions of neutrinos with matter and their densities. We study these differences in a quantum field theoretical formalism and by comparing vacuum and matter probability oscillation curves. Our main focus in the present thesis is to present a detailed analysis of these probabilities with the change in the energies, length and mixing angles. We also emphasize the role of unknown neutrino third mixing angle θ13 which is proven to be a non zero value in the recent advances . The effect of non-zero θ13 changes various other results and its accurate determination is important and hence it is important to see the effect on probabilities with large and small values of θ13 and also the effects on other parameters like CP violation, mass hierarchy etc.
M.Sc. (Physics)
Keywords: Oscillation probablity; effect of theta 13; neutrinos; interaction